(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: Studying the history and current state of the legal regulation of transplantation in ophthalmology is required for solving the issues on the subject. Purpose: To investigate the genesis of legal regulation of transplantation in ophthalmological practice, and to identify the issues and prospects for further evolution in this area. Materials and Methods: Dialectic, systemic-and-structural, comparative legal and comparative historical methods of research were used. Regulatory legal acts of the Soviet period and those of the independent Ukraine after 1991, and relevant legal practice and works of domestic and foreign scientists were examined. Results: A comparative legal study of the legal framework on transplantation in ophthalmology both in the Soviet period and that of the independent Ukraine was conducted. The basic legal regulation criteria for performing transplantation in ophthalmology were subjected to analysis. Conclusion: Periodization of the evolution of legislation for transplantation in ophthalmology was introduced. Proposals for improving current legislation on transplantation in ophthalmology were offered.